Self-enforcing trade : developing countries and WTO dispute settlement - Bown, Chad P. (Chad Philips), 1972- (Washington, D.C. : Brookings Institution Press, 2009)
"Examines challenges and costs of developing countries accessing WTO dispute settlement process. Reviews WTO's extended litigation process, highlighting areas countries have to master--international economics, law, and politics. Assesses recent efforts to help countries overcome these hurdles and proposes a solution to largest obstacle: lack of information, monitoring, and surveillance"--Provided by publisher.
The WTO and GATT : a principled history -- Developing countries, the WTO agreements, and trade liberalization -- An introduction to WTO dispute settlement -- Developing countries and WTO trade disputes -- WTO enforcement at the firm level: the extended litigation process -- The advisory centre on WTO law -- Development-focused NGOs in WTO enforcement -- Monitoring and the institute for assessing WTO commitments.
Includes bibliographical references (pages 261-272) and index.
Keywords: World Trade Organization; World Trade Organization -- Developing countries; World Trade Organization; World Trade Organization -- Studies; International trade; Foreign trade regulation; Arbitration (International law); Arbitration (International law); Foreign trade regulation; International trade; Developing countries